Effects of changing the head coach on soccer team’s performance: A systematic review - Sousa, Honorato; Clemente, Filipe; Gouveia, Élvio; Field, Adam; Sarmento, Hugo Borges (Biology of Sport, 2024)
The aim of this review was to identify and synthesise the most significant literature addressing the effects of changing the HC on soccer team’s performance, identifying the most frequently researched outcomes and characterizing their methodologies. A systematic review of PubMed, Scopus, Web of Science and SPORTDiscus databases was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA, 2020) guidelines. The following keywords and synonyms were entered in various combinations in the title, abstract or keywords: “football*” OR soccer AND “coach*” OR “manager*” AND “replacement” OR “turnover” OR “substitution*” OR “change”. Solely original articles written in English that contained data about the effects of the change in the HC on performance in professional male soccer were included. A total of 94 titles were identified, of which 24 met the eligibility criteria. The quality of the studies was considered excellent. The most common topic of analysis was the effects of the HC on match outcomes (i.e., win, draw, loss, points won, goals average). Some studies suggest that the HCs dismissal has small but positive impacts on a team’s short-term performance, while other findings suggest that little to-no impact is observed following HC departure. The dismissal of the HC does not guarantee increase success of an underperforming team. Some studies suggest that hiring an appropriate coach could positively affect match performance in the short-term. Due to limited variations in study designs, further research is needed before robust conclusions can be drawn.